El autobus magico en el cuerpo humano - Cole, Joanna; Degen, Bruce (New York : Scholastic Inc., 1991)
On a special field trip in the magic school bus, Ms Frizzle's class learn at first hand about the parts of the body and how they work.
Keywords: Body, Human; Cuerpo humano